Does Public-Sector Employment Fully Crowd Out Private-Sector Employment? - Behar, Alberto (IMF Working Papers; Working Paper ;, 2013)
We quantify the extent to which public-sector employment crowds out private-sector employment using specially assembled datasets for a large cross-section of developing and advanced countries, and discuss the implications for countries in the Middle East, North Africa, Caucasus and Central Asia. These countries simultaneously display high unemployment rates, low private-sector employment rates and high proportions of government-sector employment. Regressions of either private-sector employment rates or unemployment rates on two measures of public-sector employment point to full crowding out. This means that high rates of public employment, which incur substantial fiscal costs, have a large negative impact on private employment rates and do not reduce overall unemployment rates.